Camelid VHH affinity ligands enable separation of closely related biopharmaceuticals. Issue 2 (20th October 2016) - Pabst, Timothy M.; Wendeler, Michaela; Wang, Xiangyang; Bezemer, Sandra; Hermans, Pim; Hunter, Alan K.
Abstract: Interest in new and diverse classes of molecules such as recombinant toxins, enzymes, and blood factors continues to grow for use a biotherapeutics. Compared to monoclonal antibodies, these novel drugs typically lack a commercially available affinity chromatography option, which leads to greater process complexity, longer development timelines, and poor platformability. To date, for both monoclonal antibodies and novel molecules, affinity chromatography has been mostly reserved for separation of process‐related impurities such as host cell proteins and DNA. Reports of affinity purification of closely related product variants and modified forms are much rarer. In this work we describe custom affinity chromatography development using camelid VH H antibody fragments as "tunable" immunoaffinity ligands for separation of product‐related impurities. One example demonstrates high selectivity for a recombinant immunotoxin where no binding was observed for an undesired deamidated species. Also discussed is affinity purification of a coagulation factor through specific recognition of the gamma‐carboxylglutamic acid domain. Abstract : Separation of closely related, but less biologically active, forms of biopharmaceuticals often requires that the purification process be operated under conditions that are low‐yielding and/or manufacturing unfriendly. In this study, the authors demonstrate the use of highly selective camelid VH H affinity chromatography for the separation of active proteins from inactive protein variants that differ by as little as one amino acid or a minor change in a post‐translational modification.